SAE Technical Paper Series 2019
DOI: 10.4271/2019-01-0070
|View full text |Cite
|
Sign up to set email alerts
|

CFD Study of Heat Transfer Reduction Using Multiple Injectors in a DCEE Concept

Abstract: Earlier studies on efficiency improvement in CI engines have suggested that heat transfer losses contribute largely to the total energy losses. Fuel impingement on the cylinder walls is typically associated with high heat transfer. This study proposes a two-injector concept to reduce heat losses and thereby improve efficiency. The two injectors are placed at the rim of the bowl to change the spray pattern. Computational simulations based on the Reynolds-Averaged Navier-Stokes approach have been performed for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…No air exchange and so, no pumping losses have been taken into account in this study. More details about the methodology were reported in a previous study [12].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…No air exchange and so, no pumping losses have been taken into account in this study. More details about the methodology were reported in a previous study [12].…”
Section: Methodsmentioning
confidence: 99%
“…Another solution was proposed by Uchida et al [11] using multiple injectors. Further evaluation has been done on this concept [12] showing a heat transfer reduction of 15 % or 2 % of the fuel energy through a changed flow pattern. However, this study highlighted the issues of an omega-shaped bowl when using two injectors.…”
Section: /15/2019mentioning
confidence: 99%
See 2 more Smart Citations
“…However, this lower flame/wall interaction was not confirmed and needs to be studied further. Other computational studies have confirmed the heat loss reduction using multiple injectors [14,15]. In these studies, CFD simulations were performed to investigate how two injectors can reduce heat losses and increase the efficiency of an HD CI engine.…”
Section: Introductionmentioning
confidence: 99%